Analysis of the Activity-Based Costs of Fresh Milk Jujube Cultivation in Ban Phon Agriculture Kham Muang District, Kalasin Province - taengphukieo, Ratchada; Anchaisri, Piyarat; สารพันธ์, ณัฐพร (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The goal of this study is to examine and assess the capital costs associated with logistics in the context of the jujube plantation activity system in Ban Phon, Moo 3, Phon Sub-district, Kham Muang District, Kalasin Province. 153 farmers gathered information through interviews and surveys. Research results show that the main activities of jujube farmers in rye raw milk jujube cultivation consisted of six main activities, namely 1. Plot preparation activities. 2. Tree planting activities 3. Maintenance activities 4. Harvesting activities 5. Transportation activities and 6. Other activities. The total activity basic cost is 46,560 baht per rai. The most costly activity was maintenance, which cost 36,350 baht per rai, or 78.08% of the total cost. The following activities were undertaken: planting preparation activities, which cost 5,500 baht per rai or 11.81%; planting preparation activities, which cost 2,880 baht per rai or 6.18%; maintenance activities, which cost 1,500 baht per rai or 3.23%; other activities, which cost 230 baht per rai or 0.49%; and transportation activities, which cost 100 baht per rai or 0.21%.